Republic of Serbia : Staff Report for the 2010 Article IV Consultation, Third Review Under the Stand-By Arrangement, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2010)
This 2010 Article IV Consultation highlights that the authorities' adjustment program has contributed to limiting the fallout of the global crisis on Serbia. Although the output slump has been limited relative to regional peers, the decline in domestic demand has been significant, resulting in a strong external adjustment. The outlook for 2010 points to a slow but balanced recovery. The pickup in growth will likely be moderate, reflecting slow trading-partner recovery, protracted corporate deleveraging, nominal freezes in public wages and pensions, and lagging labor market adjustment.